DIFFERENTIAL VULNERABILITY TO EARLY-LIFE PARENTAL DEATH: THE MODERATING EFFECTS OF FAMILY SUICIDE HISTORY ON RISKS FOR MAJOR DEPRESSION AND SUBSTANCE ABUSE IN LATER LIFE* - Hollingshaus, Michael S. (Biodemography Soc Biol, 2016)
Only a portion of those exposed to parental death in early life (PDE) develop behavioral health disorders. We utilized demographic pedigree data from the Utah Population Database to test for differential vulnerability to PDE by creating a risk score of familial susceptibility to suicide (FS) at the population level. Using logistic panel regression models, we tested for multiplicative interactions between PDE and FS on the risks of major depressive disorder (MDD) and substance abuse (SA), measured with Medicare claims, after age 65. The final sample included 155,983 individuals (born 1886 through 1944), yielding 1,431,060 person-years at risk (1992 through 2009). Net of several potential confounders, including probability of survival to age 65, for females we found an FS × PDE interaction, where PDE and FS as main effects had no impact but jointly they increased MDD risk. No statistically significant main or interactive effects were found for SA among females, or for either phenotype among males. Our findings are consistent with a differential vulnerability model for MDD in females, where early-life stress increases the risk for poor behavioral health only among the vulnerable. Furthermore we demonstrate how demographic and pedigree data might serve as tools for investigating differential vulnerability hypotheses.